Analisis Manajemen Pengelolaan Zakat: Analysis of Zakat Management - Niila Luthfatul Fauziah; Ahmad Muhibin; M. Pudail; Yeni Fitriyani; Multazam Mansyur Addury (Department of Management Zakat and Waqf, 2024)
This research aims to analyze the management of zakat (Islamic almsgiving) at BAZNAS (National Amil Zakat Agency) in Magelang District, focusing on the processes of zakat collection and distribution from muzakki (zakat payer) to mustaḥik (zakat recipient). Employing a qualitative method, this study utilizes both primary and secondary data. The findings reveal adherence to prevailing legal regulations in zakat management at BAZNAS in Magelang District. Planning involves budgeting in the Annual Zakat Collection and Distribution Plan (RKAT) and conducting awareness campaigns to enhance zakat payment consciousness. Organizational structure aligns with the Magelang District Chief's decree, while implementation comprises zakat collection and distribution phases. The majority of zakat funds are sourced from civil servants (ASN) in Magelang District and distributed among 8 beneficiary groups. Supporting factors in zakat management include official directives from the Magelang District Chief, contributions from village officials, and the success of developmental initiatives in zakat collection. However, there are inhibiting factors such as the rise in retired civil servants (ASN) and the transfer of supervision of state high schools from the district government to the provincial government.